USING POWER STRATEGY TO TEACH WRITING SKILL - Reka Tia Susanti; Fitri Novia (Universitas Islam Ogan Komering Ilir Kayuagung, 2016)
Writing is an important language skill that must be learned by students. However, it is a complex process that makes many students have difficulty to generate ideas or struggle with brainstorming. As the result, their composition is not coherent and unity. POWER strategy can be used to help students’ in doing the process of writing. The objective of this study was to find out whether or not there was a significant difference in writing achievement between students who were taught through POWER strategy and that of those who were not. The quasi-experimental method was used. Purposive sampling technique was used to select the sample. The written test was used as an instrument. The t-test was used to analyze the data. Based on the data, it was found that tobtained (3.511) was higher than ttable (1.966), and pvalue (0.000) was lower than αvalue (0.05) It meant that null hypothesis (Ho) was rejected and consequently the alternative hypothesis(Ha)was accepted. Hence, there was a significant difference in writing achievement between students who were taught through POWER strategy and that of those who were not